Student study and solutions companion : Calculus, single variable - Blank, Brian E., 1953- (Key College Pub., 2005)
Calculus is one of the milestones of human thought. Every well-educated person should be acquainted with the basic ideas of the subject. As our world has become more quantified and technological, knowledge of calculus has become essential to a broader cross-section of the population. This Debut Edition of Calculus by Brian E. Blank and Steven G. Krantz, both of Washington University in St. Louis, is published in two volumes, Single Variable and Multivariable. These respected authors bring together time tested as well as innovative pedagogy and exposition in this book, focusing on today's best practices in calculus teaching.